2014
DOI: 10.7727/wimj.2013.068
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology and Psychiatric Co-morbidities in Patients Seeking Rhinoplasty for Cosmetic Reasons

Abstract: Assessment of detailed psychopathological aspects and psychiatric co-morbidities could help to define the clinical profile of people requesting cosmetic rhinoplasty in cosmetic surgery settings. Research into these factors may be important as it is essential to detect crucial problems such as personality disorders and BDD before surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 15 publications
(19 reference statements)
0
19
0
Order By: Relevance
“…Self-rated, 21 item scale 2. Second edition represents a revision that is more consistent with current diagnostic criteria for depression 103 Monpellier et al (2018) 12 Bender et al (2014) 72 Vargel et al (2001) 77 Paula et al (2018) 14 Pavan et al (2017) 104 Belli et al (2013) 7 Pavan et al (2013) 17 Beraldo et al (2016) 16 Hamilton depression rating scales (HDRS) 105 106,107 Chahraoui et al (2006) 15 Hamilton anxiety rating scales (HARS) 108 1. Clinician-based questionnaire consisting of 14 items 2.…”
Section: Management Of Body Dysmorphic Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…Self-rated, 21 item scale 2. Second edition represents a revision that is more consistent with current diagnostic criteria for depression 103 Monpellier et al (2018) 12 Bender et al (2014) 72 Vargel et al (2001) 77 Paula et al (2018) 14 Pavan et al (2017) 104 Belli et al (2013) 7 Pavan et al (2013) 17 Beraldo et al (2016) 16 Hamilton depression rating scales (HDRS) 105 106,107 Chahraoui et al (2006) 15 Hamilton anxiety rating scales (HARS) 108 1. Clinician-based questionnaire consisting of 14 items 2.…”
Section: Management Of Body Dysmorphic Disordermentioning
confidence: 99%
“…A case control study found that approximately 26% of the cases seeking rhinoplasty had at least one psychiatric diagnosis; of whom 18% had somatoform disorder, 12% had body dysmorphic disorder (BDD), 6% narcissistic personality disorder, and 6% avoidant personality disorder. 7 A large retrospective chart review of patients attending elective plastic surgery revealed that 44% had a psychiatric illness, with 50% of them having major depressive disorder and 32% having generalized anxiety disorder. 8 Below, we summarize studies reporting the prevalence of specific psychiatric illnesses among clients undergoing cosmetic surgery.…”
Section: Psychiatric Morbidity In Clients Undergoing Cosmetic Surgerymentioning
confidence: 99%
“…These results were also adapted to the study of Bili et al [14]. Bili et al conducted a study called "Psychopathology and Mental Illness among Patients who are seeking rhinoplasty surgery" and indicated that patients applying for rhinoplasty surgery have at least one of the psychological impairments [14].…”
Section: Discussionmentioning
confidence: 99%
“…Healthy mental state of applicants is deterministic in their satisfaction after cosmetic surgery [12,13]. Belli et al also suggested that the evaluation of psychiatric pathology and synergies can help define the clinical profiles of those who apply for rhinoplasty [14]. Previous studies indicated that a rhinoplasty applicant expresses greater psychopathological abnormalities [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, NPD is associated with harmful health behaviors, such as alcohol and drug use (Luhtanen and Crocker, 2005;MacLaren and Best, 2013;Hill, 2016), risky sexual behavior (Lavan and Johnson, 2002;Martin et al, 2013), and dangerous driving (Hill, 2016). Finally, NPD has been frequently found among people resorting to cosmetic and plastic surgery (Shridharani et al, 2010;Belli et al, 2013;Agostino et al, 2018).…”
Section: Introductionmentioning
confidence: 99%